(untitled) (Materiali di Estetica. Terza serie, 2017)
After a brief analysis on the Kantian influence on Schiller’s aesthetics, the paper will mainly focus on the themes concerning together Mendelssohn’s and Schiller’s philosophy in the discussion on compassion and the role of art into moral. Topics that will give the opportunity to investigate the strict relation between aesthetics and morality, particularly in the tragic art.